Some Aspects of Tricuspid Atresia - Thaher Djalil; Palupi Sunarno; Otte J. Rachman; Bambang Madiyono (Indonesian Pediatric Society, 1978)
During the period of 5 years, from the beginning of 1971 up tp the end of 1975, out of 2054 sick children seen in the Pediatric Outpatient Division of the Department of Cardiology Medical School, University of lndonesia/Dr. Cipto Mangunkusumo General Hospital Jakarta, 1073 patients were found to have congenital heant disease. Ten out of these 1073 CHD patients have been diagnosed as Tricuspid Atresia on the clinioal basis, giving the incidence of 0.93% of all CHD, of whom 5 were boys and 5 were girls, mean age being 36.5% months (range 2 months to 12 years). Hemodynamic studies have been done to 3 of the 10 patients, all of which confirmed the diagnosis. Two children went to surgery. Anatomic and radiologic classification and types of the disease in those 3 children and some clinical aspects and hemodynamic studies are discussed. It is stressed that early recognition and surgicalÂ intervention are indicated, and still should be improved.